Problematika Moralitas Anak pada Masa Pandemi Covid-19 Perspektif Immanuel Kant: Studi Kasus Di Kampung Cikaso Desa Sukamukti Kecamatan Cisompet Kabupaten Garut - Yeni Wahyuni (Jurnal Penelitian Ilmu Ushuluddin, 2021)
The purpose of this study was to analyze the problems of children's morality during the Covid-19 pandemic from the perspective of Immanuel Kant. This research is a qualitative research using descriptive methods of phenomenology and moral philosophy for a case study in Cikaso Village, Sukamukti Village, Cisompet District, Garut Regency. The findings in this research show that the impact of the Covid-19 pandemic does not only affect the health sector, but the education sector is also affected where character education and morality of children receive less attention from the policy makers. As for the point of view of Immanuel Kant's moral philosophy, explaining that morality is divided into two parts, namely hypothetical imperatives and categorical imperatives. This study concludes that the morality of children in Cikaso Village is mostly included in the hypothetical imperative. This study recommends for further and in-depth research on studies of morality, especially in the perspective of Immanuel Kant.